Mobile digital x-ray and portable cartridge based nucleic acid amplification test machines for point-of-care diagnosis of TB in rural India. (21st December 2020) - Datta, Bornali; Ford, David; Goyal, Pinky; Prakash, Ashish; Tripathy, Jaya Prasad; Gnanashanmugam, Devasena; Mishra, Sunil; Aggarwal, Ankit; Kotalwar, Sameer Gopalrao; Mittal, Sandeep; Mangla, Anshul; Jaiswal, Anand; et al.
Abstract: Background: There is no experience of point-of-care (POC) microbiological confirmation for TB in India in field settings. Methods: Under the TB-Free Haryana project, a mobile van-mounted digital x-ray and portable GeneXpert system screened all presumptive TB patients with strong clinic-radiological suspicion for TB. Results: Of 1673 x-rays, 215 (13%) had findings suggestive of TB, 109 had strong clinical suspicion and were eligible for POC GeneXpert, in whom a test was performed in 82 (75%) cases; 59 (72%) tested positive and were initiated on treatment within 24 h. Conclusions: A mobile van equipped with digital x-ray and POC GeneXpert is feasible and has a good success rate with potential for replication.